Influences on frequency and duration of game stoppages during soccer - Siegle, M.; Lames, M. (Journal of Quantitative Analysis in Sports, 2012)
The aim of the present study was to analyse game stoppages in male and female league and knock-out matches in order to gain information about possible influences on the frequency and duration of stoppages during football matches. The sample consisted of 48 matches, resulting in 5860 analysed stoppages. For each stoppage, duration, type (e.g. free kick, goal kick, etc.), mode (Knock Out vs. Round Robin), sex, and location were registered. Per match 108.06 ± 13.02, 122.50 ± 13.86, 132.38 ± 10.76, and 139.00 ± 9.94 stoppages were registered on average for male league, male World Cup, female World Cup, and female league matches, respectively. ANOVAs were calculated to analyse possible influences of the different variables. Results showed that the duration of a stoppage is significantly influenced by all four variables (p<.01). Moreover, results showed significant interactions between mode and sex (p<.01) and mode and score (p<.01). Altogether, the present study showed that game stoppages are a main part of football matches. Moreover, coaches as well as referees can use the information gained from this study.